Mobile-Based Archipelago Tourist Destination UI/UX Design as Information Media for Archipelago Tourists: Desain UI/UX Destinasi Wisata Nusantara Berbasis Mobile sebagai Media Informasi bagi Wisatawan Nusantara - Siti Masyithoh; Pratama Bayu, Widagdo (Universitas Negeri Semarang, 2024)
The National Medium Term Development Plan (RPJMN) 2020-2024 shows that 41 percent of Indonesian tourism still relies on Bali, even though Indonesia has a variety of other tourist destinations that can be exposed. This is due to the lack of information about less popular tourist destinations, thereby limiting exposure to these destinations. This study project aims to produce a mobile-based UI/UX design using a design thinking framework. The result is a UI/UX design prototype